An acellular dermal matrix allograft (Alloderm ® ) for increasing keratinized attached gingiva: A case series - Chitra Agarwal; Baron Tarun Kumar; Dhoom Singh Mehta (Wolters Kluwer Medknow Publications, 2015)
Context: Adequate amount of keratinized gingiva is necessary to keep gingiva healthy and free of infl ammation. Autografts have been used for years with great success to increase the width of attached gingiva. Autografts, however, have the disadvantage of increasing postoperative morbidity and improper color match with the adjacent tissues. Alloderm ® allograft has been introduced as an alternative to autografts to overcome these disadvantages. Aim: In this study, the efficacy of alloderm ® in increasing the width of attached gingiva and the stability of gained attached gingiva was evaluated clinically. Materials and Methods: Five patients with sites showing inadequate width of attached gingiva (≤1 mm) were enrolled for the study. The width of keratinized gingiva and other clinical parameters were recorded at baseline and 9th month postoperatively. Result: In all cases, there is the average increase of about 2.5 mm of attached gingiva and was maintained for 9-month. Percentage shrinkage of the graft is about 75% at the end of 3 rd month in all cases. Excellent colors match with adjacent tissue has been obtained. Conclusion: The study signifi es that Alloderm ® results in an adequate increase in the amount of attached gingiva and therefore can be used successfully in place of autografts.